The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1016/j.isci.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic Dissection of Oncogenically Active Epiproteomes Identifies Drivers of Proliferative and Invasive Breast Tumors

Abstract: Proliferative and invasive breast tumors evolve heterogeneously in individual patients, posing significant challenges in identifying new druggable targets for precision, effective therapy. Here we present a functional multi-omics method, interaction-Correlated Multi-omic Aberration Patterning (iC-MAP), which dissects intra-tumor heterogeneity and identifies in situ the oncogenic consequences of multi-omics aberrations that drive proliferative and invasive tumors. First, we perform chromatin activity-based chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…For example, we identified the splicing factor SF3B1 and the 40S ribosomal protein Rps14 as ET-specific G9a interactors, and Bojkova et al found that emetine inhibition of Rps14 or pladienolide inhibition of SF3B1 significantly reduced SARS-CoV-2 replication 19 . Like our finding for G9a interactors in cancer patients with poor prognosis 16 , the ChaC-MS results for ET macrophages showed that certain genes upregulated by SARS-CoV-2 infection are fully translated to their encoded proteins as ET-specific G9a interactors. Thus, constitutively active G9a may coordinate these SARS-CoV-2 activated translation pathways.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…For example, we identified the splicing factor SF3B1 and the 40S ribosomal protein Rps14 as ET-specific G9a interactors, and Bojkova et al found that emetine inhibition of Rps14 or pladienolide inhibition of SF3B1 significantly reduced SARS-CoV-2 replication 19 . Like our finding for G9a interactors in cancer patients with poor prognosis 16 , the ChaC-MS results for ET macrophages showed that certain genes upregulated by SARS-CoV-2 infection are fully translated to their encoded proteins as ET-specific G9a interactors. Thus, constitutively active G9a may coordinate these SARS-CoV-2 activated translation pathways.…”
Section: Resultssupporting
confidence: 80%
“…Accordingly, we found by top-down mass spectrometry (MS), ChIP-PCR, and ChaC chemoprobe pull-down that the methylation activity of G9a was constitutively higher in chronically inflamed or endotoxin-tolerant (TL or ET) macrophages compared with acutely inflamed (NL) cells. 14 Thus, we performed label-free quantitation (LFQ), 25,26 UNC0965 ChaC experiments 16 on mouse Raw 264.7 macrophages under nonstimulated (N) and different inflammatory conditions (NL, TL) ( Fig. 1a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More broadly, combined ChaC-MS data predicted that, via AD-phenotypic interactions with key translation regulators such as HNRNPA2B1 and other regulators of ribosomal biogenesis, G9a has a noncanonical (nonepigenetic) function in translational and post-translational regulation of AD pathogenesis. Also, to determine the clinicopathological relevance of these ChaC findings, we used our multiomics approach (iC-MAP, interaction Correlated Multi-omic Aberration Patterning) 13 to retrospectively analyze the NIH Gene Expression Omnibus databases of AD patient blood (Accession: GSE63060) 33 . We identified 26 and 47 G9a interactor mRNAs that had interactioncorrelated overexpression patterns 34 in the blood of 80 MCI and 145 AD patients, respectively, compared with a healthy population (n=104) (fig.…”
Section: Constitutively Active G9a Regulates the Translational Mechan...mentioning
confidence: 99%